Landslide susceptibility evaluation of Iruvazhinji watershed of Chaliyar River, Central Kerala, India, using frequency ratio approach - Rajappan , Suraj Plackyl; Babu, Melvin; Manoharan , A N; Manohar, Hitha (Brawijaya University, 2025)
The frequency ratio (FR) model is employed for the landslide susceptibility analysis of Iruvazhinji watershed of Chaliyar river basin, central Kerala. For the present study, slope, slope aspect, slope curvature, elevation, Slope Forming Material (SFM), drainage density, distance from river, Topographic Wetness Index (TWI), Land Use/Land Cover (LULC), and Normalised Vegetation Index (NDVI) have been considered as landslide causative factors. The spatial relationship between these factors and landslide occurrences in the study area was examined, and the results showed that SFM, elevation, and slope angle have a significant control over landslide occurrence. Using the FR algorithm, we generated a Landslide Susceptibility Map (LSM) and zonal categorization of the study area into low, moderate, high, and very high susceptibility zones. Most of these areas are classified as either high or very high susceptibility zones, reflecting a higher potential for landsliding in the study area. The validation of the susceptibility map was carried out via calculation of the Area Under the Curve (AUC) of Receiver Operating Characteristic (ROC) analysis, which points to a high level of landslide susceptibility model accuracy. The findings of this study help in land use planning, hazard mitigation, and disaster risk in vulnerable landslides, as well as support in improving resistance measures against disaster management due to landslides.